2013
DOI: 10.1371/journal.pgen.1003201
|View full text |Cite
|
Sign up to set email alerts
|

Human Disease-Associated Genetic Variation Impacts Large Intergenic Non-Coding RNA Expression

Abstract: Recently it has become clear that only a small percentage (7%) of disease-associated single nucleotide polymorphisms (SNPs) are located in protein-coding regions, while the remaining 93% are located in gene regulatory regions or in intergenic regions. Thus, the understanding of how genetic variations control the expression of non-coding RNAs (in a tissue-dependent manner) has far-reaching implications. We tested the association of SNPs with expression levels (eQTLs) of large intergenic non-coding RNAs (lincRNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
197
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(203 citation statements)
references
References 32 publications
5
197
0
1
Order By: Relevance
“…In addition to a role in shaping the development of many tissues and cells, there is a defined role for lncRNAs in differentiation of T‐cell subsets 90. Evidence of the impact of long noncoding RNAs in immune function is becoming clear,91, 92 and alterations in function can be identified in autoimmune and chronic inflammation samples which are linked to lncRNAs 93. The importance of lncRNA in Treg has been elegantly demonstrated for a lncRNA (Flicr) which subtly controls the expression of FOXP3 in mouse and human Treg 94.…”
Section: Long Noncoding Rnas and Tregmentioning
confidence: 99%
“…In addition to a role in shaping the development of many tissues and cells, there is a defined role for lncRNAs in differentiation of T‐cell subsets 90. Evidence of the impact of long noncoding RNAs in immune function is becoming clear,91, 92 and alterations in function can be identified in autoimmune and chronic inflammation samples which are linked to lncRNAs 93. The importance of lncRNA in Treg has been elegantly demonstrated for a lncRNA (Flicr) which subtly controls the expression of FOXP3 in mouse and human Treg 94.…”
Section: Long Noncoding Rnas and Tregmentioning
confidence: 99%
“…GWAS over the last decade have identified nearly 6,500 disease or trait-predisposing SNPs where only 7% of these are located in proteincoding regions of the genome [36,37] and the remaining 93% are located within non-coding areas [38,39] such as regulatory or intergenic regions. SNPs which occur in the putative regulatory region of a gene where a single base change in the DNA sequence of a potential TFBS may affect the process of gene expression are drawing more attention [40][41][42] …”
Section: Discussionmentioning
confidence: 99%
“…Genome-wide association studies (GWAS) over the last decade have identified nearly 6500 disease or trait-predisposing SNPs where only 7% of these are located in protein-coding regions of the genome [23,24] and the remaining 93% are located within non-coding areas [25,26] such as regulatory or intergenic regions. SNPs which occur in the putative regulatory region of a gene where a single base change in the DNA sequence of a potential TFBS may affect the process of gene expression are drawing more attention [7,9,27].…”
Section: Discussionmentioning
confidence: 99%